Systemic lupus erythematosus variants modulate the function of an enhancer upstream of TNFAIP3 - Pasula, Satish; Gopalakrishnan, Jaanam; Fu, Yao; Tessneer, Kandice L.; Wiley, Mandi M.; Pelikan, Richard C.; Kelly, Jennifer A.; Gaffney, Patrick M. (Frontiers in Genetics, 2022)
TNFAIP3/A20 is a prominent autoimmune disease risk locus that is correlated with hypomorphic TNFAIP3 expression and exhibits complex chromatin architecture with over 30 predicted enhancers. This study aimed to functionally characterize an enhancer 55kb upstream of the TNFAIP3 promoter marked by the systemic lupus erythematosus (SLE) risk haplotype index SNP, rs10499197. Allele effects of rs10499197, rs58905141, and rs9494868 were tested by EMSA and/or luciferase reporter assays in immune cell types. Co-immunoprecipitation, ChIP-qPCR, and 3C-qPCR were performed on patient-derived EBV B cells homozygous for the non-risk or SLE risk TNFAIP3 haplotype to assess haplotype-specific effects on transcription factor binding and chromatin regulation at the TNFAIP3 locus. This study found that the TNFAIP3 locus has a complex chromatin regulatory network that spans 1M bp from the promoter region of IL20RA to the 3’ untranslated region of TNFAIP3. Functional dissection of the enhancer demonstrated co-dependency of the RelA/p65 and CEBPB binding motifs that, together, increase IL20RA and IFNGR1 expression and decreased TNFAIP3 expression in the context of the TNFAIP3 SLE risk haplotype through dynamic long-range interactions up- and downstream. Examination of SNPs in linkage disequilibrium (D’=1.0) with rs10499197 identified rs9494868 as a functional SNP with risk allele-specific increase in nuclear factor binding and enhancer activation in vitro. In summary, this study demonstrates that SNPs carried on the 109kb SLE risk haplotype facilitate hypermorphic IL20RA and IFNGR1 expression, while suppressing TNFAIP3 expression, adding to the mechanistic potency of this critically important locus in autoimmune disease pathology.